Dukungan Orangtua dalam Proses Terapi Anak dengan Gangguan Autisme - Putri Kurniawati; Hetti Rahmawati; Diantini Viatrie (Flourishing Journal, 2021)
This research aims to determine the support that given by parents in the therapy processes for child with autism disorder based on the dynamic and dimensions of support. The qualitative research is used as a research method with case study approach model. The research subjects are used by Focus Group Discussion (FGD) in A Plus Malang therapy. Then, it obtained two pairs of participants that is two pairs of parents who had followed the FGD. Data was collected by in-depth interviews to two pairs of participants. Another data collection is observation during the interview and documents studied which as child assessment result. Data analysis techniques are using thematic analysis and validity research is using triangulation or checking participant perspective. The result of the research shows the parents roles are divided into, the role of father and mother that are equally supportive and forming pattern of parental support in therapy processes for child with autism disorder. There are some dimensions of support in the therapy processes for child with autism disorder that are, Emotional support or appreciation of giving reward, emotional support or appreciation in showing love for child, emotional support or appreciation to response of other to the child, emotional support or appreciation during the therapy processes, instrumental support fulfillment the needs of child, informational support of information search, informational support give direction to the child, and friendship support. The dimensions of support influence the development of the child in undergoing the therapy processes. ZL parents tend to give a low support level to the child in the therapy processes. Meanwhile, in the SG parents give a high level of support to the child in the therapy processes. The support levels are viewed based on the dimensions of support and treatment provided by parents of child. Penelitian ini bertujuan untuk mengetahui dukungan yang diberikan oleh orangtua dalam proses terapi anak dengan gangguan autisme berdasarkan dinamika serta dimensi-dimensi dukungannya. Metode penelitian yang digunakan adalah penelitian kualitatif dengan model pendekatan studi kasus. Metode pengambilan subjek penelitian menggunakan Focus Group Discussion (FGD) yang dilaksanakan di tempat terapi A Plus Malang. Kemudian diperoleh 2 pasang partisipan yaitu, dua pasang orangtua yang telah mengikuti FGD. Pengumpulan data dilakukan dengan wawancara mendalam (in depth interview) pada kedua pasang partisipan. Pengumpulan data yang lain adalah observasi pada saat wawancara berlangsung, dan studi dokumen yaitu, hasil asesmen anak. Teknik analisis data menggunakan analisis tematik dan cek keabsahan data penelitian menggunakan triangulasi perspektif atau cek partisipan dan cek tema- tema yang menyimpang. Hasil penelitian menunjukkan bahwa peran orangtua terbagi menjadi, peran ayah dan peran ibu yang sama-sama mendukung dan membentuk pola dukungan orangtua dalam proses terapi anak dengan gangguan autisme. Beberapa dimensi dukungan dalam proses terapi anak dengan gangguan autisme yaitu, dukungan emosional atau penghargaan pemberian reward, dukungan emosional atau penghargaan menunjukkan rasa cinta pada anak, dukungan emosional atau penghargaan terhadap respon orang lain pada anak, dukungan emosional atau penghargaan selama menjalani proses terapi, dukungan instrumental pemenuhan kebutuhan anak, dukungan informasional pencarian informasi, dukungan informasional memberikan arahan pada anak, dan dukungan persahabatan. Dimensi-dimensi dukungan tersebut mempengaruhi perkembangan sang anak dalam menjalani proses terapinya. Orangtua ZL cenderung memiliki tingkat dukungan yang rendah diberikan pada anak dalam proses terapi. Sedangkan, pada orangtua SG memiliki tingkat dukungan yang tinggi diberikan pada anak dalam proses terapinya. Tingkat dukungan dilihat berdasarkan dimensi dukungan dan penanganan yang diberikan oleh orangtua pada sang anak.